RELAÇÕES FLORÍSTICO-GEOGRÁFICAS NA ESTRUTURA DE UMA FLORESTA NA REGIÃO CENTRAL DO RIO GRANDE DO SUL, BRASIL - Sühs, Rafael Barbizan; Putzke, Jair; Budke, Jean Carlos (Floresta, 2010)
Normal 0 21 false false false PT-BR X-NONE X-NONE MicrosoftInternetExplorer4 Normal 0 21 false false false PT-BR X-NONE X-NONE MicrosoftInternetExplorer4 Normal 0 21 false false false PT-BR X-NONE X-NONE MicrosoftInternetExplorer4 Normal 0 21 false false false PT-BR X-NONE X-NONE MicrosoftInternetExplorer4 /* Style Definitions */ table.MsoNormalTable mso-style-name:"Tabela normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman","serif"; ResumoO presente estudo verificou a influência dos contingentes florísticos sobre a composição e estrutura de uma sinúsia florestal na região central do Rio Grande do Sul, Brasil. O estudo foi realizado no município de Sinimbu, em uma floresta decidual, onde foram demarcadas 100 unidades amostrais contíguas, totalizando 1 ha. Todos os indivíduos com diâmetro à altura do peito ≥ 4,8 cm foram amostrados e identificados. As famílias com maior riqueza específica foram Myrtaceae (18), Fabaceae (16) e Euphorbiaceae (10). A maior parte das espécies e dos indivíduos amostrados é de ampla distribuição geográfica. Uma elevada proporção das espécies pertenceu ao contingente das florestas estacionais, entretanto, este apresentou baixo número de indivíduos. O contingente Atlântico apresentou, além de um baixo número de indivíduos, também baixa riqueza. A comunidade apresentou três estratos de altura, todos com predominância de plantas de ampla distribuição geográfica.Palavras-chave: Fitogeografia; flora; unidade de conservação; vale do Rio Pardo. AbstractFloristic-geographic relationships in a forest structure at the central region of the State of Rio Grande do Sul, Brazil. This work studied the influence of floristic contingents on the composition and structure of a forest in the central region of the State of Rio Grande do Sul, Brazil. The study was carried out in the County of Sinimbu, in a deciduous forest, where 100 contiguous sampling units that totaled 1 ha were established. All individuals with DBH ≥ 4,8 cm were identified and measured. The richest families were Myrtaceae (18), Fabaceae (16) and Euphorbiaceae with 10 species. Most of the species surveyed are widely distributed across southern Brazilian vegetation formations. A large proportion of species belonged to the western seasonal contingent, although it has had contributed with few individuals. The eastern wet contingent presented both, low percentage of species and individuals. The community showed three height layers, all of them showing dominance of wide geographical distribution species.Keywords: Phytogeography; flora; conservation unit; Rio Pardo valley.